2006
DOI: 10.1542/peds.2005-2869
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Prevention and Cessation Intervention Delivery by Pediatric Providers, as Assessed With Patient Exit Interviews

Abstract: Pediatric providers who receive training and reminders to deliver a brief smoking prevention and cessation intervention to adolescents in the context of routine pediatric primary care practice can do so feasibly and with a high degree of fidelity to the intervention protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 47 publications
0
25
0
1
Order By: Relevance
“…More than one of the above frameworks informed the study in 2 (3.6%) of the 55 reviewed studies [46, 52], with a maximum of 3 frameworks being used, none of them being the BCC framework. In 4 studies (7.3%), there was no suggestion that a framework had been considered [32, 72, 77, 84]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…More than one of the above frameworks informed the study in 2 (3.6%) of the 55 reviewed studies [46, 52], with a maximum of 3 frameworks being used, none of them being the BCC framework. In 4 studies (7.3%), there was no suggestion that a framework had been considered [32, 72, 77, 84]. …”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies (43 studies, 78.2%) included only a subjective assessment of receipt (i.e. collected on intervention deliverers or recipients) [2530, 3237, 3942, 45, 47, 49, 50, 52–55, 57, 5963, 6572, 74, 75, 77, 78, 84]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19] It is unknown, however, whether these findings are generalizable to younger patients, as there have been fewer studies among adolescents in primary care. 25,26 Existing studies suggest that primary care screening and brief interventions can positively impact adolescent health issues, such as tobacco use, [27][28][29][30] nutrition and physical activity, 31,32 and depression. 33,34 A large longitudinal study of 14-year-old primary care patients 26 found that screening and brief provider counseling significantly increased helmet use but did not reduce adolescent alcohol or drug use, suggesting the need to explore supplemental strategies to enhance effectiveness, such as the computerized education component that occurs before the provider visit in the cSBA system.…”
mentioning
confidence: 99%
“…Nevertheless, the majority of adolescents make at least one healthcare visit each year, and these missed opportunities have been noted by advocates [45]. Pediatricians who have had specific training in smoking cessation are more likely to talk to adolescents about cessation as are those who believe that their advice is likely to be effective [43,46]. As with parenting smokers, low rates (17%) of NRT prescription by pediatricians for smoking teens are reported [47].…”
Section: Smoking Cessation Counseling For Adole-scents In the Pediatrmentioning
confidence: 99%